Family responsibilities and women's working lives - Austen, Siobhan; Birch, Elisa (Curtin University of Technology, 2000)
As a result of changing social norms and economic imperatives many Australianwomen are now participating in the paid workforce. This paper discusses howwomen in Australia juggle their dual roles of employee and carer. It canvasseschanges in government policies and workplace practices that support women'sworking lives and examines the impact of women's family responsibilities ontheir social and economic status.